IMPLEMENTATION OF CHILDREN FRIENDLY SCHOOL TO REALIZE JAVANESE CULTURAL CHARACTER BASED SOCIAL ENVIRONMENT - Siti Supeni (GeoEco, 2020)
The research aims at analyzing the needs of children friendly schools in implementing local culture based character education to realize good social environment based on Javanese cultural character and producing the model of developing local culture based character education to realize good social environment. The methods of collecting the data are interview, survey, observation, and documentation. The technique in analyzing the data is research and development model. The researcher would like to describe the research result during the 1st year in Surakarta City Central Java Indonesia. The research findings show that the needs of children friendly schools in implementing local culture based character education are persistent guidance and assistance for students to create and practice local culture, workshops and seminars for students and teachers in training to preserve local culture, the needs to complete the model for children friendly school that contains benefits, purposes, materials, and technical activities. The conclusion of the research is that the needs of children friendly city in implementing local culture are compulsory to realize social environment based on Javanese culture and to support the implementation of the model for children friendly city.